Ferroptosis involves in renal tubular cell death in diabetic nephropathy - Wang, Yue; Bi, Ran; Quan, Fei; Cao, Qiuhua; Lin, Yanting; Yue, Chongxiu; Cui, Xinmeng; Yang, Hongbao; Gao, Xinghua; Zhang, Dayong (European journal of pharmacology, 2020)
Ferroptosis is a novel type of programmed cell death characterized by iron-dependent accumulation of lipid hydroperoxides to lethal levels. Accumulative studies have indicated diabetic nephropathy (DN) as an inflammatory disorder, which involved immune modulation both in the occurrence and progression of the disease. In addition, DN is also considered as the major threatening complication of Diabetes mellitus (DM). However, other forms of programmed cell death, such as autophagy, apoptosis and necrosis, have been reported to be associated with DN, while there are no effective drugs to alleviate the damage of DN. In this study, we explored whether ferroptosis was involved in the progression of DN both in vivo and in vitro. We first established DN models using streptozotocin (STZ) and db/db mice. Results showed significant changes of ferroptosis associated markers, like increased expression levels of acyl-CoA synthetase long-chain family member 4 (ACSL4) and decreased expression levels of glutathione peroxidase 4 (GPX4) in DN mice. Also lipid peroxidation products and iron content were increased in DN mice. Next, in vitro, ferroptosis inducer erastin or RSL3 could induce renal tubular cell death, while iron and high ACSL4 levels sensitised ferroptosis. Finally, ACSL4 inhibitor rosiglitazone (Rosi) was used in the development of DN, which improved survival rate and kidney function, reduced lipid peroxidation product MDA and iron content. In summary, we first found ferroptosis was involved in DN and ferroptosis might be as a future direction in the treatment of DN. A proposed schema for ferroptosis involving in renal tubular cell death in diabetic nephropathy. In this research, we explored whether ferroptosis was involved in the progression of DN both in vitro and in vivo. As a result, significant changes of ferroptosis associated markers, like increased expression levels of ACSL4 and decreased expression levels of GPX4 in DN mice. Also lipid peroxidation products and iron content were increased in DN mice. ACSL4 inhibitor rosiglitazone (Rosi) could improve survival rate and kidney function through alleviating ferroptosis and reducing proinflammation factors such as IL-6, TNF-α and Ptgs2. [Display omitted]